Pengaruh Financial Behaviour, Experienced Regret, Dan Mental Accounting Terhadap Keputusan Investasi Pada Crypto (Studi Pada Investor Crypto Di Kota Malang) - Nizam, Muhammad Sahrun; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The increasing needs of society have led people to start thinking about what they will need in the future. One way to address this is through investment, with various forms of investment now available, one of which is crypto. The number of crypto investors has also grown, indicating that public interest and participation in crypto investments are high. This study aims to determine the extent of the influence of Financial Behaviour, Experienced Regret, and Mental Accounting on investment decisions in a study of crypto investors in Malang City. This research employs an explanatory research type. The sampling technique used is non-probability sampling with a purposive sampling method. The sample size was determined using the Maholtra formula, resulting in 75 respondents. Data processing was conducted using multiple linear regression analysis with the assistance of SPSS version 25. The results of this study indicate that the financial behaviour variable has a positive and significant effect on crypto investment decisions, the experienced regret variable has a positive but not significant effect on crypto investment decisions, and the mental accounting variable has a positive and significant effect on crypto investment decisions. Keywords: Financial Behavior, Experienced Regret, Mental Accounting, Investment Decisions